Marketing Strategy Of Tutoring Services With New Branding Of Former Primagama License In Bekasi Regency 2025 - Saputra, Nico Albarino; Sahela, Zeisha (Jurnal Fokus Manajemen, 2025)
The growth of the non-formal education sector in the capital city’s buffer zones has created intense competition among similar institutions. Following the expiration of the Primagama brand license, this institution faces challenges in rebuilding its brand image while simultaneously attracting new students. This study aims to analyze and formulate effective marketing strategies for the former Primagama tutoring institution in Bekasi Regency. The research employs a qualitative approach with a case study method, focusing on the ex-Primagama tutoring institution. The subjects of the study include institutional managers, students, and parents. Data were collected through in-depth interviews, operational observations, and documentation studies consisting of promotional materials, activity reports, and registration records. Source and method triangulation were applied to enhance the validity and reliability of the findings. The data were analyzed using thematic analysis techniques through iterative stages of data reduction, data presentation, and conclusion drawing. The findings reveal that the key factors for successful marketing strategies include improving service quality, utilizing digital marketing, gathering positive reviews, rebranding, and innovating in learning programs. These strategies have proven effective in attracting new students and strengthening institutional competitiveness. The results highlight the importance of consistent implementation, regular evaluation, and the development of technology-based curricula to ensure the institution remains adaptive to market demands. This research is expected to provide both practical and theoretical contributions to the development of marketing strategies in the non-formal education sector in the digital era.